Athletic retirement: factors contributing to sleep and mental health problems - Montero, Ashley; Baranoff, John; Adams, Robert; Drummond, Murray (Frontiers in Psychology, 2024)
Introduction The aim of this investigation was to determine which factors were associated with symptoms of sleep and mental health disorders in former athletes. Methods Former athletes (N = 173, 50% women) who retired from any competition level within the last 20 years participated in an online survey. The survey consisted of the Athlete Sleep Screening Questionnaire (ASSQ), Personal Wellbeing Index-Adult (PWI-A), Center for Epidemiologic Studies Depression Scale-Revised (CESD-R), and Generalised Anxiety Disorder Assessment (GAD-7). Results Binary logistic regressions revealed that both age (OR = 0.95 [95% CI:0.92, 0.99], p = 0.007) and gender (OR = 2.28 [95% CI:1.09, 4.79], p = 0.029) were associated with anxiety, with women and younger ex-athletes presenting greater risk of anxiety symptoms. Higher body mass was associated with an increased risk for sleep difficulty (OR = 1.13 [95% CI:1.03, 1.23], p = 0.008), sleep disordered breathing (OR = 1.20 [95% CI:1.10, 1.30], p < 0.001), and compromised wellbeing (OR = 0.89 [95% CI:0.83, 0.96], p = 0.001). Athletes who subjectively placed a lower priority on sport while competing presented greater risk of sleep disordered breathing (OR = 2.00[95% CI:1.05, 3.80], p = 0.035). No associations between recency retirement and any outcome measures were observed. Discussion Findings suggest potential predictive factors for difficulty transitioning out of sport. Future longitudinal research should consider the interplay between sport re-engagement and the incidence and chronicity of sleep and mental health disorders.